Efficacy and Safety of Carbetocin in Comparison to Oxytocin for the Prevention of Primary PPH during Caesarean Section: An Open Label Randomized Control Trial - Kabir, Nazneen; Ara, Begum Hosne; Akter, Dilruba; Daisy, Tahmina Afrin; Jesmin, Sonia; Razzak, Mollika; Begum, Hasina; Islam, GM Raihanul (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Background: Postpartum hemorrhage (PPH) is a potentially life-threatening complication of both vaginal and caesarean delivery. The most frequent cause of postpartum hemorrhage is uterine atony, when the uterus fails to contract fully after delivery of the placenta. For the prevention of this uterine atony we need an effective uterotonic drug. Till now oxytocin is used for enhancing uterine contraction after delivery. But oxytocin has some limitations like shorter halflife, less contraction time and more side effects, whereas carbetocin has prolonged duration of action which ensures more contraction time and less adverse effects. So, carbetocin considered as a good alternative over oxytocin for the prevention of primary PPH in caesarean section. The Aim of Study: To see the efficacy and safety of carbetocin over oxytocin for the prevention of primary PPH during caesarean section. Patients and Methods: A randomized-controlled trial was conducted in the Institute of Child and Mother Health (ICMH), Dhaka, Bangladesh over a period of nine months from January to September 2016. Ninety-four patients who had got admitted in ICMH undergoing caesarean section at term were randomized into two groups receiving either 10IU oxytocin or 100μg carbetocin, after the operation. Outcome measures such as primary PPH, massive blood loss, need for additional uterotonic drug, additional blood transfusion as well as adverse effects were all documented. Results: This study had shown that carbetocin is superior in comparison to oxytocin for the prevention of primary PPH following caesarean section. Each patient obtained either a single dose of 100 microgram carbetocin intravenously or 10 IU of oxytocin during caesarean section. Massive blood loss occurred in 6.4%patients, blood transfusion needed in 17% patients and additional uterotonic needed for 25.5% patients in oxytocin group but in carbetocin group no massive blood loss occurred, only 2.1% patient needed immediate blood transfusion and no patient was required additional uterotonics. There were no major adverse effects observed in both the groups. No patients had developed PPH in carbetocin group. But 12.8% patients had developed primary PPH in oxytocin group. Conclusion: Carbetocin appears to be an effective new drug than oxytocin for the prevention of primary postpartum hemorrhage in caesarean section. J Bangladesh Coll Phys Surg 2019; 37(1): 19-24